Advanced bioactive nanomaterials for biomedical applications. Issue 3 (28th December 2021) - Zhao, Yu; Zhang, Zhanzhan; Pan, Zheng; Liu, Yang
Abstract: Bioactive materials are a kind of materials with unique bioactivities, which can change the cellular behaviors and elicit biological responses from living tissues. Bioactive materials came into the spotlight in the late 1960s when the researchers found that the materials such as bioglass could react with surrounding bone tissue for bone regeneration. In the following decades, advances in nanotechnology brought the new development opportunities to bioactive nanomaterials. Bioactive nanomaterials are not a simple miniaturization of macroscopic materials. They exhibit unique bioactivities due to their nanoscale size effect, high specific surface area, and precise nanostructure, which can significantly influence the interactions with biological systems. Nowadays, bioactive nanomaterials have represented an important and exciting area of research. Current and future applications ensure that bioactive nanomaterials have a high academic and clinical importance. This review summaries the recent advances in the field of bioactive nanomaterials, and evaluate the influence factors of bioactivities. Then, a range of bioactive nanomaterials and their potential biomedical applications are discussed. Furthermore, the limitations, challenges, and future opportunities of bioactive nanomaterials are also discussed. Abstract : In this review, we summary the recent advances of bioactive nanomaterials, and discuss the influence factors of bioactivities including the physical structure of bioactive nanomaterials, surface properties, and nanotopography. Then, a range of bioactive nanomaterials, including inorganic nanomaterials, carbon‐based nanomaterials, polymeric nanomaterials, and supramolecular‐based nanomaterials are discussed. In addition, we also introduce several typical applications of bioactive nanomaterials, including wound healing, cancer therapy, neurodegenerative disease therapy, and biocatalyst.